The application and impact of artificial intelligence in the field of animation as well as the existing disadvantage - Jia, Haoran (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper provides an in-depth look at the application and impact of Artificial Intelligence (AI) in the animation industry, while also pointing out the existing limitations. In recent decades, AI has been seamlessly integrated into all aspects of life, and the field of animation creation is no exception.AI has not only automated tedious tasks, increased efficiency, and lowered costs, but also revolutionized the traditional animation ecosystem by providing animators with entirely new ways of expression. With the rapid advancement of digital technology, AI has become a key driver of innovation and change, especially in creative industries. In the animation industry, the introduction of AI technology has not only reinvigorated the traditional craft, but also opened up unprecedented creative possibilities. This paper explores the specific applications of AI in animation production, such as automatically rendering the texture of animation to help animators complete repetitive tasks. Or the use of algorithms to assist in the production of special effects and color modification. Through the animation creator’s description to complete the modeling, or through deep learning, machine learning generated large models to assist the character’s behavioral design and so on. While AI brings many opportunities to the field of animation, it also comes with the challenge of ethical considerations and the risk of possible substitution of traditional technologies. the application of AI in animation has pushed the industry in the direction of greater efficiency, innovation, and personalization, and has also prompted us to think deeply about the combination of creativity and technology.